Chondrogenic differentiation potential of adult and fetal equine cell types. Issue 3 (25th February 2019) - Adam, Emma N.; Janes, Jennifer; Lowney, Rachael; Lambert, Joshua; Thampi, Parvathy; Stromberg, Arnold; MacLeod, James N.
Abstract: Objective: To determine the chondrogenic potential of cells derived from interzone tissue, the normal progenitor of articular cartilage during fetal development, compared to that of adult bone marrow‐derived and adipose‐derived mesenchymal cell isolates. The objective of this study was to compare the chondrogenic potential of fetal musculoskeletal progenitor cells to adult cell types, which are currently used therapeutically to facilitate joint cartilage repair in equine clinical practice. The hypothesis tested was that cells derived from interzone tissue have a chondrogenic potential that exceeds that of adult bone marrow‐derived and adipose‐derived mesenchymal cell isolates. Study design: In vitro study. Animals: Six young adult horses (15–17 months of age) and 6 equine fetuses aged 45–46 days of gestation. Methods: Three‐dimensional pellet cultures were established under chondrogenic conditions with fresh, primary cells isolated from adult (articular cartilage, bone marrow, adipose, dermis) and fetal (interzone, skeletal anlagen cartilage, dermis) tissues. Cellular morphology, pellet architecture, and proteoglycan synthesis were assessed in the pellet cultures. Steady state levels of ACAN (aggrecan core protein), COL2A1 (collagen type II), and COL1A1 (collagen type I) messenger RNA (mRNA) were compared among these cell types as pellet cultures and monolayer cultures. Results: Adult articular chondrocytes, fetal interzone cells, and fetal anlage cells generated the largest pellets under these chondrogenic culture conditions. Pellets derived from adult articular chondrocytes and fetal anlage cells had the highest scores on a neocartilage grading scale. Fetal anlage and adult articular chondrocyte pellets had low steady‐state levels of COL1A mRNA but high COL2A1 expression. Anlage chondrocyte pellets also had the highest expression of ACAN . Conclusion: Adult articular chondrocytes, fetal interzone cells, and fetal anlage chondrocytes exhibited the highest chondrogenic potential. In this study, adult adipose‐derived cells exhibited very limited chondrogenesis, and bone marrow‐derived cells had limited and variable chondrogenic potential. Clinical significance: Additional investigation of the high chondrogenic potential of fetal interzone cells and anlage chondrocytes to advance cell‐based therapies in diarthrodial joints is warranted.